Trends of Climate Change in Some Selected Districts of Western Nepal - Upadhayaya, Rajedra Prasad; Baral, Madhab Prasad (Janapriya Journal of Interdisciplinary Studies, 2020)
Climate change is a global threat that has particularly strong impacts on countries whose economies are highly dependent on agriculture and still developing--like Nepal. The main objective of this study is to assess the trend of climate change in Gandaki Province, Nepal. This study is based on secondary data. It utilizes the data from the Department of Hydrology and Meteorology between 1970- 2018 based on eight districts with 10 different stations ranging from 110m. to 2680m. in Gandaki Province. Mann-Kendall test and Sen’s slope is used to find the trend. The analyses reveal that trend of maximum temperature is increasing and significant. The maximum temperature trend is 0.08°C/year in monsoon and post-monsoon which is greater than the global rate. The minimum temperature trend is positive and significant and is highest in the monsoon season (0.04°C/year). The trend of the average rainfall sum is insignificant and is positive only in pre-monsoon and negative in other seasons, which indicates erratic rainfall that causes floods and droughts.